Model Konseptual Untuk Keterlibatan Orang Tua, Sikap Siswa, Kebijakan Sekolah, dan Prestasi Siswa dalam Pembelajaran Agama Islam - Idaya Andriani; Irfan Qowwiyul Aziz Alhahajj; Sri Wahyu Sihombing; Irwan Fathurrochman (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to construct a conceptual model by testing influential relationships among parental engagement, Students’ attitudes towards Islamic religious learning, school policies, and student academic achievement. Using PLS-SEM, six hypotheses modeled based on the interactions of the four variables were analyzed. 500 students from Madrasah Aliyah Negeri (MAN) located in Bengkulu were recruited using a convenient sampling technique. Data were collected using a valid and reliable questionnaire and analyzed based on measurement models and structural models. This research found a significant influence of variables related to Islamic religious learning. The analysis showed that parental engagement had a big impact on Students’ attitudes (original sample value: 0.698, T-statistics: 23.268, p-values: 0.000), school policies (original sample value: 0.327, T-statistics: 12.332, p-values: 0.000), and students’ achievements in learning Islamic religion (original sample value: 0.224, T-statistics: 6.984, p-values: 0.000). Apart from that, students' attitudes also contributed significantly to school policies and their academic achievement in learning Islamic religion (original sample value: 0.147, T-statistics: 5.871, p-values: 0.000). School policies were also proven to substantially influence students’ achievements in religious learning (original sample value: 0.536, T-statistics: 8.498, p-values: 0.000). These results emphasize that the model has been well-established and well-confirmed, demonstrating the important roles of parental engagement, Students’ attitudes, and school policies in advancing Islamic religious education. Keywords: parental engagement, students’ attitudes, school policies, and students’ achievements in Islamic religious learning